2012
DOI: 10.1063/1.4726116
|View full text |Cite
|
Sign up to set email alerts
|

Experimental isolation of degradation mechanisms in capacitive microelectromechanical switches

Abstract: DC and bipolar voltage stresses are used to isolate mechanical degradation of the movable electrode from charging mechanism in microelectromechanical capacitive switches. Switches with different metals as the movable electrode were investigated. In titanium switches, a shift in the pull-in voltages is observed after dc stressing whereas no shift occurs after the bipolar stressing, which is to be expected from charging theory. On switches with similar dielectric but made of aluminium, the narrowing effect occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…6 In this paper, it will be shown that by extending this method to include monitoring the recovery characteristics of the device pull-in, further isolation and identification of individual mechanical degradation mechanisms may be achieved.…”
Section: 3mentioning
confidence: 99%
“…6 In this paper, it will be shown that by extending this method to include monitoring the recovery characteristics of the device pull-in, further isolation and identification of individual mechanical degradation mechanisms may be achieved.…”
Section: 3mentioning
confidence: 99%
“…We have previously demonstrated a microelectromechanical switch for use in telecommunications applications, and have reported elsewhere on the RF performance, lifetime and reliability of the device [9][10][11]. Four types of switch have been investigated here, consisting of 100 × 100 μm 2 and 200 × 200 μm 2 aluminum membranes suspended on either meander or straight springs above a coplanar waveguide that is coated by a thin (130 nm) layer of silicon oxide dielectric.…”
Section: Switch Design and Fabricationmentioning
confidence: 99%
“…Mechanical degradation of this membrane decreases the magnitude of all threshold voltages resulting in a narrowing of the device capacitancevoltage (CV) characteristic. [2][3][4] Another reliability concern is caused by the accumulation of charge inside the dielectric layer when an electric field stress is applied. As a result of dielectric charging the device CV curve will shift depending on the polarity of the dielectric charge.…”
mentioning
confidence: 99%
“…16 Therefore, it can be very difficult to isolate both mechanisms when only changes of the CV characteristic are used to characterize device reliability. However, an electrical test method has recently been developed, 3 which allows mechanical degradation to be studied in isolation using only changes in the CV curve. 16 A noncontact method has also been investigated to reduce the effect of mechanical degradation on dielectric charging measurements.…”
mentioning
confidence: 99%